MANAJEMEN SISTEM PENILAIAN KINERJA GURU TAMAN KANAK-KANAK DENGAN SIMPLE ADDITIVE WEIGHTING - Lewa, Andi Hallang; Farida, Ida; Setiawan, Aries; Hariyadi, Guruh Taufan; Suharnawi, Suharnawi; Purwatiningsih, Aris Puji (Jurnal Transformatika, 2024)
Teacher performance according to Law Number 14 of 2005 includes the main activities of planning, learning, implementing, assessing learning outcomes, mentoring and training children as well as additional tasks related to the main activities in accordance with the main workload. Teacher performance influences student learning outcomes, with good teacher performance it should produce good quality students as well. Therefore, it is natural that teacher performance needs to be measured every period. The assessment certainly contains the main and additional tasks. Based on these problems, it is also necessary to improve the existing performance appraisal system. There needs to be an appropriate method to assist the teacher performance assessment process, one of which is the weighted method, namely simple additive weighting (SAW). Performance assessment every semester using the SAW method will be able to bridge the results of increasingly better teacher performance. The assessment is carried out on a weighted basis for each parameter. The final result is a ranking of the performance of all teachers in descending order